"The Button": Initiating the Patient–Nurse Interaction. (April 2014) - Lasiter, Sue
Patient–nurse interactions are foundational to care that is desired by patients. Evidence about patient-initiated interactions with nurses is scant and little focus has been placed on the meaning to patients of ways to call for help when needed. The purpose of this secondary analysis was to provide a more intensive focus on initiative, one of four categories identified in a grounded theory study related to the perception of feeling safe in intensive care. Of 10 participants, a subset of 9 participant interviews was included in this analysis. Participants perceived "the button" was a way to initiate interaction with a nurse and to get the help they might need "right now." This report emphasizes the importance of nurse call lights to patients and contributes to evidence focused on the meaning for patients of initiating interaction with nurses. Findings have important implications for care quality and nurse education.